Characteristics of horizontal force generation for individuals post-stroke walking against progressive resistive forces. Issue 1 (January 2015) - Wang, Jing; Hurt, Christopher P.; Capo-Lugo, Carmen E.; Brown, David A.
Abstract Background Walking, while experiencing horizontal resistive forces, can allow researchers to assess characteristics of force generation in a task specific manner for individuals post-stroke. Methods Ten neurologically nonimpaired individuals (mean age 52 years) and fourteen chronic stroke survivors (mean age 54 years) with hemiparesis walked in the treadmill-based KineAssist Walking and Balance System, while experiencing twelve progressive horizontal resistive forces at their comfortable walking speed. Slope coefficients of the observed force–velocity relationship were quantified and submitted to an iterative k-means cluster analysis to test for subgroups within the post-stroke sample. Extrapolated force values for individuals were quantified by extrapolating the line of best fit of the force–velocity relationship to the x-intercept. Findings Within the post-stroke group, six individuals were clustered into a high sensitivity group, i.e., large reduction in speed with resistance, and eight were clustered into a low sensitive group, i.e., small reduction in speed with resistance. The low sensitivity group was similar to non-impaired individual. The extrapolated force was significantly higher for non-impaired individuals compared to individuals post-stroke in either the high or low sensitivity group. The differences between low and high sensitivity group suggest that high sensitivity of walking speed to applied resistive force is indicative of overall weakness. Interpretation Individuals with high sensitivity to horizontal resistive force may be walking at or near their maximum force generating capacity when at comfortable walking speed, while low sensitivity individuals may have greater reserve force generating capacity when walking at a particular comfortable walking speed.